Pemanfaatan Aplikasi Duolingo dalam Meningkatkan Penguasaan Kosakata Bahasa Inggris - Salsa Dwi Puspita; Shahnaz Lulu Amanda; Vivia Nasya Swara; Zia Ash Shaffa (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The development of digital technology has brought innovation in language learning, one of which is through the Duolingo application in improving English vocabulary mastery. The method used is quantitave with surveytechniques, involving 111 respondents, from various levels of education, the majority of college student (88,3%). The resukts showed that 84,7% of respondents had used Duolingo, with the majority using it for less than a month. The most helpful features in vocabulary learning are listening exercise (74.8%), speaking (67,6%), reading (68,5%), and writing (58,8%). Most responden felt that duolingo was quite effective in improving language skills, especially in the aspects of reading and listening. However, there are several obstacles such as the presence of advertisemnts, limited life systems, and lack of variation in vocabulary. Overall, Duolingo is an interactive and interesting lerning media, although it still needs further development to be more optimal in improving language skills. The study provides insight into the role of technology in language learning and can be a reference for the development of similar applications in the future